The effect of vulvar lichen sclerosus on quality of life and sexual functioning - Helvacioglu, Özlem; Topkarcı, Zeynep; Helvacıoğlu, Çağlar; Kavak, Ayşe (Journal of Surgery and Medicine, 2021)
Background/Aim: Vulvar lichen sclerosus (VLS) is a chronic inflammatory condition that has the potential to cause sexual dysfunction and reduction in patients’ life quality. We aimed to evaluate the quality of life and sexual function in female patients with VLS. Methods: This prospective case-control study was conducted with women who presented to the gynecology clinic with a biopsy-proven diagnosis of VLS or for routine gynecological check-ups between June 2017-January 2018. The patients were grouped according to the presence or absence of VLS. Effects of VLS on quality of life and sexual functions were analyzed with the Dermatology Life Quality Index (DLQI) and Female Sexual Function Index (FSFI) questionnaires. Results: A total of 86 women were included in this study. Thirty-seven VLS patients were compared with 49 patients without VLS. The total DLQI scores of the VLS and control groups were 6.14 (6.87) and 1.92 (2.41), respectively (P=0.001), and the total FSFI scores, 15.42 and 24.22, respectively (P<0.001). Sub-group analyses revealed that the two groups significantly differed in terms of sexual desire, arousal, orgasm, satisfaction, and pain (P<0.001), but not in terms of lubrication (P=0.741). Conclusion: Vulvar lichen sclerosus negatively affects the quality of life and sexual function. Questionnaires such as DLQI and FSFI are useful tools for the assessment of sexual function and quality of life in these patients. Since these patients may be hesitant to report their sexual problems, healthcare professionals should interrogate them in this regard during the early stages of management.